A hybrid framework for sustaining and managing Somali indigenous knowledge - Jama Madar , Mohamed; Ahmed Sulub, Mohamed; A Omar, Abdisamad (Journal of Advanced Computer Science & Technology, 2024)
This paper represents the important of preserving Somali Indigenous Knowledge for the future generations to come. This paper presents a systematic review of the indigenous knowledge Management Systems deployed for different sectors in Africa and other countries in the world. The acquisition and management of IK is being used to rejuvenate endangered cultural practices and improve domestic socio-economic sustainability of Somali society. This paper presents how social media platforms and their components could be integrated into the KMS to manage and sustain Somali Indigenous knowledge (IK). The discovery of knowledge and its utilization is now fueled by the advancement of technology, which connects users to external sources through different platforms. The rapidly increasing use of SM and mobile technologies creates opportunities to form knowledge networks that can facilitate the process of creating, preserving, and sharing knowledge and skills that are unique to communities in the Somali context. As an oral society with rich IK and other cultural practices, Somali society lacked a framework to organize the existing knowledge in various methods. We used knowledge products from journal articles, policy documents, working papers, policy briefs, and other gray literature. The paper refers to existing methodology E-learning and KM functions. If properly integrated, this method first identifies functional similarities between SM, E-Learning, and KM systems and their interactions. The proposed framework consists of two functional parts; KM and SM. The KM part involves knowledge capturing, validation, formatting, storing, and distribution. SM part of the framework involves knowledge presentation, sharing, and application. Since the Somalis are said to be an oral society, this framework helps to capture and disseminate IK residing in knowledge holders.